A Study of Co-articulation in Stuttering - Suchitra M.G (Journal of All India Institute of Speech and Hearing, 1970)
In spite of the theoretical simplicity and appeal of the notion that stuttering reflects a lack of co-articulation, it has received little recent empirical support. The purpose of the present study was to analyze the extent of first and second formant transitions in the fluent and disfluent speech of stutterers and to compare thiswith the fluent utterances of normal speakers.